6+9h=20+2h

Simple and best practice solution for 6+9h=20+2h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+9h=20+2h equation:


Simplifying
6 + 9h = 20 + 2h

Solving
6 + 9h = 20 + 2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-2h' to each side of the equation.
6 + 9h + -2h = 20 + 2h + -2h

Combine like terms: 9h + -2h = 7h
6 + 7h = 20 + 2h + -2h

Combine like terms: 2h + -2h = 0
6 + 7h = 20 + 0
6 + 7h = 20

Add '-6' to each side of the equation.
6 + -6 + 7h = 20 + -6

Combine like terms: 6 + -6 = 0
0 + 7h = 20 + -6
7h = 20 + -6

Combine like terms: 20 + -6 = 14
7h = 14

Divide each side by '7'.
h = 2

Simplifying
h = 2

See similar equations:

| c=15(47) | | 4-a/6=-16 | | f(x)=-14x^3+9x^2-2 | | 0.02(y-3)+0.14=0.04y-0.03(30) | | 4a^2+24a+36=0 | | 3*-12=36 | | 0.2x+7.2=5.9 | | (x+1)(x-1)=5(x+1) | | 5x-4(-x+8)=-31 | | 5x^2-x-54=0 | | 0.02(y-4)+0.14y=0.04y-0.03(30) | | 29-5x=4+7x | | 2*(x^2)+3*x-2000=0 | | x/6-4=16 | | 5x-x-54=0 | | 6(x-6)+6=3(x-7) | | (x-3)(2x+3)=5 | | -6(0.1x+0.4)-1.3=-0.1 | | 5x^2+13x-1= | | -3+7(x-1)=12x+2-5x | | 4x+6=42-2x | | 1-7=x-x | | .58y-.25=2y-1.7 | | -2(2x-1)+7=-4x+9 | | -8x+15=-10x+5 | | n-7=3 | | 7x-3(6-x)=16 | | 4x-1=-2x+11 | | 41=16-6-x | | n-4=20 | | 4z-1=2x+11 | | -4(x+5)-6=-26 |

Equations solver categories